2012
DOI: 10.1186/2044-5040-2-24
|View full text |Cite
|
Sign up to set email alerts
|

Injectable polyethylene glycol-fibrinogen hydrogel adjuvant improves survival and differentiation of transplanted mesoangioblasts in acute and chronic skeletal-muscle degeneration

Abstract: BackgroundCell-transplantation therapies have attracted attention as treatments for skeletal-muscle disorders; however, such research has been severely limited by poor cell survival. Tissue engineering offers a potential solution to this problem by providing biomaterial adjuvants that improve survival and engraftment of donor cells.MethodsIn this study, we investigated the use of intra-muscular transplantation of mesoangioblasts (vessel-associated progenitor cells), delivered with an injectable hydrogel biomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 29 publications
3
91
0
Order By: Relevance
“…There was a tendency for a higher tissue maturity of the PEG-fib hydrogel treated wounds after 14 days in the middle of the defect. This confirms previous results of in vitro studies with PEG-hydrogels [21,42]. Differentiation of newly built tissue is also supported by the fact that a basal membrane [50] was visible in all sections of the PEG-fib hydrogel treated and untreated control wounds at the 14 days' time point.…”
Section: Survival Time -7 Dayssupporting
confidence: 78%
See 4 more Smart Citations
“…There was a tendency for a higher tissue maturity of the PEG-fib hydrogel treated wounds after 14 days in the middle of the defect. This confirms previous results of in vitro studies with PEG-hydrogels [21,42]. Differentiation of newly built tissue is also supported by the fact that a basal membrane [50] was visible in all sections of the PEG-fib hydrogel treated and untreated control wounds at the 14 days' time point.…”
Section: Survival Time -7 Dayssupporting
confidence: 78%
“…This is in accordance with other in-vivo experiments where PEG-fib hydrogel biomaterials with progenitor cells were injected into the tibialis anterior muscle of mice [42]. It was shown that the PEG-fib hydrogels provided immediate protection from host inflammation for the implant progenitor cells.…”
Section: Survival Time -7 Dayssupporting
confidence: 75%
See 3 more Smart Citations